Macrophage-Derived Extracellular Vesicles Induce Long-Lasting Immunity Against Hepatitis C Virus Which Is Blunted by Polyunsaturated Fatty Acids - Cai, Chengcong; Koch, Benjamin; Morikawa, Kenichi; Suda, Goki; Sakamoto, Naoya; Rueschenbaum, Sabrina; Akhras, Sami; Dietz, Julia; Hildt, Eberhard; Zeuzem, Stefan; Welsch, Christoph; Lange, Christian M. (Frontiers in Immunology, 2018)
Extracellular vesicles (EVs) are increasingly recognized as important mediators of intercellular communication. In the present study we aimed to further characterize the role of macrophage-derived EVs in immune responses against hepatitis C virus (HCV) and the potential of polyunsaturated fatty acids to modulate this modality of innate immunity. To this end, EVs were isolated from interferon-stimulated macrophage cultures or from plasma of patients with acute or chronic hepatitis C. EVs were characterized by electron microcopy, flow cytometry, RNA-sequencing and Western blot analyses. The effect of EVs on replication of HCV was assessed in co-culture models. Functional analyses were performed to assess the impact of polyunsaturated fatty acids on EV-mediated antiviral immunity. We found that macrophages secreted a variety of cytokines shortly after stimulation with type I and II IFN, which orchestrated a fast but short-lasting antiviral state. This rapid innate immune answer was followed by the production of macrophage-derived EVs, which induced a late, but long-lasting inhibitory effect on HCV replication. Of note, exposure of macrophages to polyunsaturated fatty acids (PUFAs), which are important regulators of immune responses, dampened EV-mediated antiviral immune responses. Finally, EVs from patients with hepatitis C exhibited long-lasting antiviral activities during IFN-therapy as well. The antiviral effect of EVs from Caucasian and Japanese patients differed, which may be explained by different nutritional uptake of PUFAs. In conclusion, our data indicate that macrophage-derived EVs mediate long-lasting inhibitory effects on HCV replication, which may bridge the time until efficient adaptive immune responses are established, and which can be blunted by PUFAs.